2019
DOI: 10.1038/s41586-019-1082-x
|View full text |Cite
|
Sign up to set email alerts
|

Innate lymphoid cells support regulatory T cells in the intestine through interleukin-2

Abstract: Interleukin (IL)-2 is a pleiotropic cytokine that is necessary to prevent chronic inflammation in the gastrointestinal tract 1 – 4 . The protective effects of IL-2 involve the generation, maintenance and function of regulatory T cells (Tregs) 4 – 8 , and low-dose IL-2 has emerged as a potential therapeutic strategy in inflammatory bowel disease (IBD) patients 9 . However, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
158
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(164 citation statements)
references
References 30 publications
5
158
0
1
Order By: Relevance
“…Finally, Fenton et al showed that the frequency of αVβ8 + cDC2, which are thought to induce Tregs, doubled in Crohn's patients compared to controls (266). However, intestinal Treg frequency among CD4 + T cells decreased in Crohn's patients (306). Nevertheless, given recent evidence that enhancing the ability of intestinal T cells to sense active TGFβ is effective in inducing remission in some Crohn's patients (307), boosting the αVβ8-TGF-β pathway may be an attractive complementary therapeutic approach to weaken inflammatory T cell responses (266).…”
Section: Function Of Intestinal Mucosa Cdc Subsetsmentioning
confidence: 99%
“…Finally, Fenton et al showed that the frequency of αVβ8 + cDC2, which are thought to induce Tregs, doubled in Crohn's patients compared to controls (266). However, intestinal Treg frequency among CD4 + T cells decreased in Crohn's patients (306). Nevertheless, given recent evidence that enhancing the ability of intestinal T cells to sense active TGFβ is effective in inducing remission in some Crohn's patients (307), boosting the αVβ8-TGF-β pathway may be an attractive complementary therapeutic approach to weaken inflammatory T cell responses (266).…”
Section: Function Of Intestinal Mucosa Cdc Subsetsmentioning
confidence: 99%
“…Moreover, upregulation of apoptotic signals has been reported in ILC3s induced by plasmacytoid dendritic cell (pDC)‐derived interferon upon HIV in humanized mice. Microbiota triggered IL‐2 production by ILC3 has just recently been shown to support Tregs . It is tempting to speculate that loss of IL‐2 producing ILC populations may have a direct effect on T‐cell homeostasis in HIV infection.…”
Section: Microbiota – Ilc Axis During Infectious Diseasesmentioning
confidence: 99%
“…Microbiota triggered IL-2 production by ILC3 has just recently been shown to support Tregs. 142 It is tempting to speculate that loss of IL-2 producing ILC populations may have a direct effect on T-cell homeostasis in HIV infection.…”
Section: Lentiviruses: Human Immunodeficiency Virus and Simian Immunomentioning
confidence: 99%
“…In addition, induction of ILC3-derived IL-22 by adherent microbiota triggers epithelial cell regulation of IL-17 production by intestinal T cells (54). Under homeostatic conditions, commensal microbiota and IL-1β also stimulate ILC3 production of GM-CSF as well as IL-2, which act via nonredundant pathways to promote intestinal Tregs (137,138). Antigen processing and presentation by MHC II + ILC3s provide a mechanism for antigen-specific regulation of commensal-specific T cells (139).…”
Section: Ilc Regulation Of Adaptive Immunity and T Cell Inflammationmentioning
confidence: 99%
“…While IL-1β can trigger splenic ILC3 expression of CD80 and CD86 to support T cell activation (140), the absence of these costimulatory molecules on intestinal ILC3s limits homeostatic T cell activation (141). Under an inflammatory microenvironment such as IBD, these regulatory mechanisms are reduced (138,141). Moreover, increased TL1A, which is highly expressed by MNPs in IBD, can induce robust expression of the costimulatory molecule OX40L on MHC II + ILC3s and drive colonic T cell-dependent inflammation (85).…”
Section: Ilc Regulation Of Adaptive Immunity and T Cell Inflammationmentioning
confidence: 99%